ANTIOXIDANT AND SUPPRESSIVE EFFECTS ON THE SYNTHESIS OF NITRIC OXIDE AND PROSTAGLANDIN E2 BY THE ETHANOLIC-EXTRACTS OF CARTHAMUS TINCTORIUS L. FLOWER - Lee, J.; Kim, G. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Carthamus tinctorius L., belongs to Compositae family, has been used as a folk medicine for the potent tyrosine inhibitory activity and the clinical treatments of osteoporosis and rheumatism in Korea. In this study, we investigated the flower-extracts of Carthamus tinctorius L. (CFEs) for an antioxidant activity and the inhibitory influence on the nitrite production and prostaglandin E2 synthesis, which are involved in the progress of the acute inflammation. The choloroform-extract (CFCE) and n-butanol-extract (CFBE) showed more than 70% scavenging activity of DPPH free radical (100 Âµg/mL). Additionally, the total ethanol extract (CHEE) had approximately 24% of DPPH radical scavenging activities, but hexane extract (CFHE) had no antioxidant activity. Cytotoxicity on RAW 264.7 macrophage cells was not shown in less than 50 or 250 Âµg/mL concentration of CFEs. CFEs had inhibited LPS-induced nitrite production in a dose-dependent manner. CFEE (250 ug/mL), CFCE (50 ug/mL), and CFHE (250 ug/mL) had suppressed approximately 70, 64, and more than 98% of LPS-induced nitrite production effectively in RAW 264.7 macrophage cells, respectively. In addition, CFEs did not show the chemical nitric oxide (NO) quenching activity in the cell-free system, but markedly inhibited the inducible nitric oxide synthase (iNOS) mRNA transcription in LPS-stimulated RAW 264.7 cells. In addition, the pretreatment with CFEs attenuated prostaglandin E2 synthesis and cyclooxygenase-2 (COX-2) gene transcription in LPS-stimulated RAW 264.7 cells. These results suggest that CFEs may exert the potential anti-inflammatory activity through the suppression of inhibitory mediators (NO and PGE2), caused by inhibition of iNOS and COX-2 gene transcription in RAW 264.7 cells.